2021
DOI: 10.3390/nano11081893
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Response of Glucose Oxidase Adsorbed on Laser-Induced Graphene

Abstract: Carbon-based electrodes have demonstrated great promise as electrochemical transducers in the development of biosensors. More recently, laser-induced graphene (LIG), a graphene derivative, appears as a great candidate due to its superior electron transfer characteristics, high surface area and simplicity in its synthesis. The continuous interest in the development of cost-effective, more stable and reliable biosensors for glucose detection make them the most studied and explored within the academic and industr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“…As a comparison, the PaperLIG/GOx/Nafion (0.5%) biosensor was also prepared and measured in the PBS using the amperometric method under −90 mV ( Figure S5a ). Previously, it was reported that graphene material can facilitate the DET (direct electron transfer) of GOx, which might be employed to develop the third generation glucose biosensor [ 52 , 53 , 54 ]. As the co-enzyme of GOx, it was reported that the redox potential for FAD on the LIG electrode is around −485 mV [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a comparison, the PaperLIG/GOx/Nafion (0.5%) biosensor was also prepared and measured in the PBS using the amperometric method under −90 mV ( Figure S5a ). Previously, it was reported that graphene material can facilitate the DET (direct electron transfer) of GOx, which might be employed to develop the third generation glucose biosensor [ 52 , 53 , 54 ]. As the co-enzyme of GOx, it was reported that the redox potential for FAD on the LIG electrode is around −485 mV [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previously, it was reported that graphene material can facilitate the DET (direct electron transfer) of GOx, which might be employed to develop the third generation glucose biosensor [ 52 , 53 , 54 ]. As the co-enzyme of GOx, it was reported that the redox potential for FAD on the LIG electrode is around −485 mV [ 54 ]. As demonstrated in Figure S5 , no obvious current response could be observed, which indicated that under applied potential (−90 mV) the direct electron transfer from the enzyme to the electrode was not feasible and the usage of a mediator was necessary.…”
Section: Resultsmentioning
confidence: 99%
“…From Figure 4 , the highest glucose oxidation peak current is obtained at pH 7.4. In addition, as the PBS solution pH (5 to 8.5) was gradually increased, the glucose oxidation peak potential was positively shifted, which indicates that protons are involved in the electrode processes [ 41 , 42 ]. These results indicate that pH of 7.4 results in higher glucose oxidation current, and it was used for further optimization studies.…”
Section: Resultsmentioning
confidence: 99%
“…39 The values of α of the system electrodes are estimated for the oxidation of glucose. The values of formal standard potential (E 0 / ) are estimated from the yintercept of the linearly fitted line of the peak potential (E p ) vs scan rate (ν) plot 40 (supplied in Fig. S3).…”
Section: Resultsmentioning
confidence: 99%